Time-dependent changes in distribution of basic fibroblast growth factor immunoreactive cells in hippocampus after kainic acid injection in rat pups - ERCAN, FERİHA; ONAT, FİLİZ; YANANLI, HASAN RACİ; ŞİRVANCI, SERAP (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Five-day-old Wistar albino rats were injected with kainic acid (KA) or saline i.p. to investigate time-dependent alterations in morphology and number of basic fibroblast growth factor (bFGF) immunoreactive (-ir) astrocytes and neurons in hippocampus at 15, 30, and 90 days after the injections. Sections were stained with cresyl violet for morphological evaluation and bFGF immunohistochemistry was used for quantitative evaluation of bFGF-ir cell density. Fifteen days after KA injection, there was gliosis but no neuronal loss although disorganization in CA1, CA3, CA4 pyramidal layers and neuronal loss were evident 30 and 90 days after the injection. KA injected rats demonstrated significantly increased number of bFGF-ir astrocytes throughout the hippocampus and pyramidal neurons in CA2 after 15 days and decreased number of bFGF-ir cells after 30 and 90 days. The decrease in the number of bFGF-ir astroglia and neurons in long term after KA injection may indicate a decrease in the production of bFGF and/or number of bFGF-ir cells suggesting that protective effects of bFGF may be altered during epileptogenesis in hippocampus. (c) 2007 ISDN. Published by Elsevier Ltd. All rights reserved.
Keywords: bFGF; hippocampus; kainic acid; immature; immunohistochemistry; TEMPORAL-LOBE EPILEPSY; BROWN-NORWAY RAT; KAINATE INJECTION; NERVOUS-SYSTEM; BRAIN; SEIZURES; NEURONS; REORGANIZATION; INDUCTION; SCLEROSIS